2021
DOI: 10.1128/aac.01341-21
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Use and Bacterial Infection among Inpatients in the First Wave of COVID-19: a Retrospective Cohort Study of 64,691 Patients

Abstract: Background: Hospitalized patients with SARS-CoV-2 infection (COVID-19) often receive antibiotics for suspected bacterial co-infection. We estimated the incidence of bacterial co-infection and secondary infection in COVID-19 using clinical diagnoses to determine how frequently antibiotics are administered when bacterial infection is absent. Methods: We performed a retrospective cohort study of inpatients with COVID-19 present on admission to hospitals in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 37 publications
3
29
1
3
Order By: Relevance
“…The exception was mechanical ventilation, which seemed to be protective, probably because of the depletion of susceptible patients, a selection bias typical of survival analysis. Furthermore, in contrast to other reports [ 46 , 47 ], we found that antibiotic consumption had a negative impact on HAIs acquisition although heterogeneously between classes of antibiotics and across periods. Interestingly, we found glycopeptides and macrolides among the protective factors; these were mostly prescribed in COVID-19 patients because of their therapeutic effect against SARS-CoV-2 pneumonia [ 48 , 49 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The exception was mechanical ventilation, which seemed to be protective, probably because of the depletion of susceptible patients, a selection bias typical of survival analysis. Furthermore, in contrast to other reports [ 46 , 47 ], we found that antibiotic consumption had a negative impact on HAIs acquisition although heterogeneously between classes of antibiotics and across periods. Interestingly, we found glycopeptides and macrolides among the protective factors; these were mostly prescribed in COVID-19 patients because of their therapeutic effect against SARS-CoV-2 pneumonia [ 48 , 49 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, the few studies that do report on UTIs are solely based on microbiological diagnostic criteria, neglecting the importance of clinical diagnostic criteria [ 18 ]. Appropriateness studies focusing on UTI diagnoses and treatment are scarce, especially in the COVID-19 setting [ 6 , 9 , 14 , 21 , 22 ]. Reyes et al came with a warning concerning probable overdiagnosis and overtreatment of asymptomatic bacteriuria in COVID-19 patients, as they cited the Infectious Disease Society of America (IDSA), which recommends ‘the assessment for other causes and watchful observation of older patients with functional and/or cognitive impairment with bacteriuria and without local genitourinary symptoms rather than immediate antimicrobial treatment’.…”
Section: Discussionmentioning
confidence: 99%
“…Since the start of the pandemic, different studies have highlighted disproportional antimicrobial use in COVID-19 patients despite low bacterial co- and superinfection rates. Reported rates vary from 4 to 19%, depending on the geographical setting of the study, the inclusion or exclusion of patients admitted to the intensive care unit and the used definitions of co-/superinfections [ 4 , 5 , 6 , 7 , 8 , 9 ]. Most investigators differentiate between bacterial respiratory co-/superinfection and nonrespiratory co-/superinfection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the publication of the retrospective study by Baghdadi and colleagues about bacterial infections and antibiotic use among coronavirus disease 2019 (COVID-19) patients ( 1 ), we have some concerns that we would like to report.…”
Section: Letter To the Editormentioning
confidence: 99%